Group Cognitive Rehabilitation and Exposure/Sorting Therapy: A Pilot Program - Ayers, Catherine R. (Cognit Ther Res, 2017)
While cognitive-behavioral therapy for hoarding disorder (HD) has resulted in significant reductions in symptoms, most individuals continue to have significant hoarding symptoms following treatment. This investigation sought to extend the literature on the behavioral treatments for hoarding by examining (1) group cognitive rehabilitation and exposure/sorting therapy (CREST) and (2) group exposure therapy (ET) for hoarding. Participants in both studies reported significant decreases in hoarding symptom severity from baseline to post-treatment on all primary outcome measures using mixed-effects linear regression models with the intent to treat sample. Participants who received group CREST reported statistically significant reductions in anxiety, depression, and overall severity at post-treatment, while participants who received group ET did not. Results provide preliminary evidence for both group CREST and group ET as effective treatments for hoarding disorder.